2018
DOI: 10.1155/2018/8765149
|View full text |Cite
|
Sign up to set email alerts
|

Delaware Inland Bays and Market Oyster (Crassostrea virginica) Quality for Consumption

Abstract: Consumption of raw oysters is known to cause serious health conditions due to bioaccumulation of contaminants. As filter feeders, oysters ingest bacteria along with phytoplankton from their surrounding habitats. Ensuring seafood safety for human consumption is always a concern. Since oysters are consumed raw, disease causing organisms, environmental contaminants, toxins, chemicals, and even physical hazards such as soils and metals retained in the oysters can enter through feeding. The objective of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…Spearman’s rank correlation analysis showed that water temperature is positively and significantly ( P < 0.05) correlated to the total V . parahaemolyticus (log 10 CFU/g or mL) levels in oyster and seawater samples ( Table 4 ), which is in agreement with previous studies [ 58 , 61 63 ]. Salinity had no significant correlation with total V .…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Spearman’s rank correlation analysis showed that water temperature is positively and significantly ( P < 0.05) correlated to the total V . parahaemolyticus (log 10 CFU/g or mL) levels in oyster and seawater samples ( Table 4 ), which is in agreement with previous studies [ 58 , 61 63 ]. Salinity had no significant correlation with total V .…”
Section: Resultssupporting
confidence: 93%
“…time, study site, and water parameters (temperature and salinity) for oyster and seawater samples, respectively. Spearman's rank correlation analysis showed that water temperature is positively and significantly (P < 0.05) correlated to the total V. parahaemolyticus (log 10 CFU/g or mL) levels in oyster and seawater samples (Table 4), which is in agreement with previous studies [58,[61][62][63]. Salinity had no significant correlation with total V. parahaemolyticus (log 10 CFU/g or mL) levels in oyster and seawater samples (Table 4).…”
Section: Plos Onesupporting
confidence: 90%
See 2 more Smart Citations
“…Texture profile in terms of hardness, cohesiveness, adhesiveness, springiness, gumminess, chewiness of fish fillet (three fish/treatment) were analysed by texture analyser TVT 6700 (PerkinElmer, Inc., Waltham, Middx, USA) and TexCal texture analyser software (version 5.0) 62 . Each sample was run in triplicate and expressed as force per g. Fillet colour coordinates (L*, a*, b*) were determined by calibrated BYK spectro-guide sphere gloss (BYK-Gardener USA, Columbia, MD, USA) 63 . 4 g of fillet were homogenized with 40 mL of distilled water and pH was determined in triplicate by Aqua-pH meter (TPS Pty Ltd, Brendale, QLD, AU) after calibrating at three-scale pH (pH 4, 7, 10) 64 .…”
Section: Methodsmentioning
confidence: 99%